Developing marketing materials through interactive learning media suitable for vocational school - Vena Melliyani; Gia Nurapni; Fajar Sidik (Curricula: Journal of Curriculum Development, 2023)
This research aims to explore and develop marketing materials that are suitable for Vocational High School (SMK) 45 Lembang students through interactive learning media. Marketing is an important aspect in the business world that requires deep understanding and practical skills. In the context of vocational school education, the use of interactive learning media is considered an effective approach to increase students' understanding and involvement in the learning process, and this can also be useful if they want to continue their education at tertiary institutions where the domain is not much different from before. This research used a qualitative approach with descriptive methods focused on developing material through appropriate interactive learning media at SMK 45 Lembang to ensure that the material produced aligned with their needs and expectations. Data was collected using observation and interviews to students and teachers based on Google forms. The research objects were students at business vocational high schools and teachers who taught marketing courses.